Integrating ESG and Maqashid Syariah for Sustainable Islamic Finance in Indonesia - Delta Khairunnisa; Suhel; Imam Asngari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The global financial sector has shifted toward sustainability, emphasizing environmental, social, and governance principles alongside ethical frameworks like Islamic law objectives. This study explores the integration of environmental, social, and governance principles with Islamic law objectives to develop sustainable Islamic financial investment strategies in Indonesia. As the world’s largest Muslim-majority country, Indonesia offers significant potential for aligning these principles with its growing Islamic finance market. The research employs a qualitative approach, utilizing a systematic literature review and thematic content analysis to examine relevant academic articles, institutional reports, and policy documents. Findings reveal a strong conceptual alignment between environmental, social, and governance principles and Islamic law objectives, particularly in environmental preservation, social justice, and ethical governance. Practical applications include Green Sukuk, with Indonesia issuing over six billion dollars since 2018, and waqf sukuk, supporting social welfare projects. However, challenges such as low awareness and regulatory gaps hinder broader adoption. This study proposes a conceptual framework to integrate these principles, enhancing Indonesia’s position as a global leader in sustainable Islamic finance. This study recommends collaboration among regulators, industry players, and academics to develop standardized guidelines, fostering a financial ecosystem that balances profitability, ethical values, and sustainability.